(untitled) (Polis (Santiago), 2018)
This article refers primarily to the initial modeling of psychology following natural sciences, and travels the path by which these sciences themselves found their limits and conditions for its transformation. This has led to an emerging paradigm that brings a new concept of "scientific objectivity", and also a different theory of rationality, which helps us overcome the cognitive antinomies and highlights the complementary and not contradictory character of experimental sciences and human sciences. This will permit, says the author, to achieve an integrated whole, coherent and logical.